Dimensi Vertikal Komunikasi Ilahi: Studi Pola Interaksi Manusia dengan Allah SWT dalam Al-Qur’an - Mahardhika Sastra Nasution; Abdullah (Samsara Institute Publisher, 2025)
The vertical dimension of divine communication describes the interaction between humans and Allah SWT which is reflected in the Qur'an. This research aims to explore the patterns of interaction that occur in such communication, with an emphasis on verses that describe aspects of prayer, revelation, and commands from God. The methodology used in this study is a qualitative approach with thematic interpretation techniques, which involves the collection and analysis of relevant Qur'anic verses. The findings of this study show that the divine communication contained in the Qur'an has distinctive characteristics, which emphasizes the importance of human sincerity, obedience, and dependence on Allah SWT. These patterns not only reflect spiritual relationships, but also provide guidance for humanity in living their daily lives with full awareness of the Divine presence and command